2010
DOI: 10.1002/pbc.22738
|View full text |Cite
|
Sign up to set email alerts
|

Cancer at ages 15–29 years: The contrasting incidence in India and England

Abstract: Incidence of cancer at ages 15-29 years in England is higher at most sites than in India. Variation in environmental exposures between the two countries might be an explanation. Under-ascertainment of cases and gender bias in seeking healthcare may also influence reported incidence rates in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…However, among the young male population there was no apparent latitude trend in melanoma incidence (2Á7%, P = 0Á41), despite the significant negative trend overall in this age group (À5Á8%, P = 0Á002; not shown). In men aged over 30 years, melanoma incidence significantly increased with more southerly latitudes: by 10Á0% per latitude rank for [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] year olds, by 20Á2% in those aged 50-69 years and by 23Á8% in 70-89 years olds (all P < 0Á0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among the young male population there was no apparent latitude trend in melanoma incidence (2Á7%, P = 0Á41), despite the significant negative trend overall in this age group (À5Á8%, P = 0Á002; not shown). In men aged over 30 years, melanoma incidence significantly increased with more southerly latitudes: by 10Á0% per latitude rank for [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] year olds, by 20Á2% in those aged 50-69 years and by 23Á8% in 70-89 years olds (all P < 0Á0001).…”
Section: Resultsmentioning
confidence: 99%
“…While lack of access to sunny holidays cannot explain this observation, London's highly urban environment perhaps affords its residents less opportunity for exposure to ambient sunlight than those of neighbouring southern regions. Notwithstanding their uneven geographical distribution, the overall proportion of nonwhites in the total population of England is small, 34 and this inference method has been used previously. A further possible explanation is the low registration rate of melanomas in the Thames Registry, possibly as a result of greater use in London of private healthcare facilities where cancer data may not be readily available to registration.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest more favorable incidence trends in some countries while in others the incidence of CM is still rising [14][15][16][17][18][19] . Recent evidence suggests that the current rising trend in incidence of CM is due to improved surveillance techniques and early diagnosis, together with changes in lifestyle in terms of excessive recreational exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that gastric cancer is much more common among people at ages of 15-29 years in Europe compared to those of the same age group in developing countries. It has been associated with nutrition and specially with high consumption of salt (Arora et al, 2010;Kono and Hirohata, 1996;Hirohata and Kono, 1997). Accumulated genetic or epigenetic alterations in a wide range of genes that control cell division, cell differentiation and cell death are the main cause of cancer (Sandberg, 1991;Parkin et al, 2001;Kono & Hirohata, 1996;Hirohata & Kono, 1997).…”
Section: Discussionmentioning
confidence: 99%